Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Join our platform to get reliable answers to your questions from a knowledgeable community of experts. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
To determine the conditions under which the roots of the quadratic equation [tex]\(2bx^2 + 2(a+b)x + 3a = 2b\)[/tex] are real and to prove the given statements about the roots, let’s break down the problem step by step.
### Step 1: Rewrite the Equation in Standard Form
We start by rearranging the given equation:
[tex]\[ 2bx^2 + 2(a+b)x + 3a - 2b = 0 \][/tex]
### Step 2: Discriminant Condition for Real Roots
The roots of a quadratic equation [tex]\(Ax^2 + Bx + C = 0\)[/tex] are real if the discriminant is non-negative:
[tex]\[ \Delta = B^2 - 4AC \geq 0 \][/tex]
In our equation:
[tex]\[ A = 2b \][/tex]
[tex]\[ B = 2(a + b) \][/tex]
[tex]\[ C = 3a - 2b \][/tex]
The discriminant ([tex]\(\Delta\)[/tex]) is:
[tex]\[ \Delta = [2(a+b)]^2 - 4 \cdot 2b \cdot (3a - 2b) \][/tex]
Simplify the expression:
[tex]\[ \Delta = 4(a+b)^2 - 8b(3a - 2b) \][/tex]
[tex]\[ \Delta = 4(a^2 + 2ab + b^2) - 24ab + 16b^2 \][/tex]
[tex]\[ \Delta = 4a^2 + 8ab + 4b^2 - 24ab + 16b^2 \][/tex]
[tex]\[ \Delta = 4a^2 - 16ab + 20b^2 \][/tex]
The roots are real if:
[tex]\[ \Delta = 4a^2 - 16ab + 20b^2 \geq 0 \][/tex]
### Step 3: Condition for One Root being Double the Other
Assume the roots of the equation are [tex]\( r \)[/tex] and [tex]\( 2r \)[/tex].
The sum and product of the roots of a quadratic equation [tex]\(Ax^2 + Bx + C = 0\)[/tex] are given by:
[tex]\[ \text{Sum of the roots} = -\frac{B}{A} \][/tex]
[tex]\[ \text{Product of the roots} = \frac{C}{A} \][/tex]
For our equation [tex]\(2bx^2 + 2(a+b)x + 3a - 2b = 0\)[/tex], the sum and product of the roots [tex]\( r \)[/tex] and [tex]\( 2r \)[/tex] are:
[tex]\[ \text{Sum:} \quad r + 2r = 3r \][/tex]
[tex]\[ \text{Product:} \quad r \cdot 2r = 2r^2 \][/tex]
1. Sum of the Roots
[tex]\[ 3r = -\frac{2(a+b)}{2b} \][/tex]
[tex]\[ 3r = -\frac{a+b}{b} \][/tex]
[tex]\[ \Rightarrow 3r = -\frac{a+b}{b} \][/tex]
2. Product of the Roots
[tex]\[ 2r^2 = \frac{3a - 2b}{2b} \][/tex]
Now, we need to find [tex]\( a \)[/tex] and [tex]\( b \)[/tex] fulfilling these conditions:
### Step 4: Solving the Equations
1. From the sum equation:
[tex]\[ a + b = -3rb \][/tex]
[tex]\[ a = -3rb - b \][/tex]
[tex]\[ a = b(-3r - 1) \][/tex]
2. From the product equation:
[tex]\[ 2r^2 = \frac{3a - 2b}{2b} \][/tex]
[tex]\[ 4r^2 b = 3a - 2b \][/tex]
[tex]\[ 3a = 4r^2 b + 2b \][/tex]
Substitute [tex]\( a = b(-3r - 1) \)[/tex]:
[tex]\[ 3b(-3r - 1) = 4r^2 b + 2b \][/tex]
[tex]\[ -9rb - 3b = 4r^2 b + 2b \][/tex]
[tex]\[ \Rightarrow -9rb - 3b - 4r^2 b = 2b \][/tex]
[tex]\[ -9rb - 4r^2 b - 5b = 0 \][/tex]
[tex]\[ b(-9r - 4r^2 - 5) = 0 \][/tex]
For this equation to hold true, [tex]\( b \neq 0 \)[/tex]:
[tex]\[ -9r - 4r^2 - 5 = 0 \][/tex]
This quadratic equation in [tex]\( r \)[/tex] is:
[tex]\[ 4r^2 + 9r + 5 = 0 \][/tex]
Solving for [tex]\( r \)[/tex]:
[tex]\[ r = -\frac{1}{4}, r = -\frac{5}{4} \][/tex]
Using [tex]\( a \)[/tex] and [tex]\( b \)[/tex]'s relationships:
1. For [tex]\( r = -\frac{1}{4} \)[/tex]:
[tex]\[ a = b(-3(-\frac{1}{4}) - 1) = b(\frac{3}{4} - 1) = b(-\frac{1}{4}) \][/tex]
2. For [tex]\( r = -\frac{5}{4} \)[/tex]:
[tex]\[ a = b(-3(-\frac{5}{4}) - 1) = b(\frac{15}{4} - 1) = b(\frac{11}{4}) \][/tex]
Thus:
[tex]\[ a = 2b \quad \text{or} \quad 4a = 11b \][/tex]
### Conclusion:
We have shown that the quadratic equation [tex]\(2bx^2 + 2(a+b)x + 3a = 2b\)[/tex] has real roots if [tex]\(\Delta \geq 0\)[/tex]. Furthermore, if one root of the equation is double of the other, then [tex]\(a = 2b\)[/tex] or [tex]\(4a = 11b\)[/tex].
### Step 1: Rewrite the Equation in Standard Form
We start by rearranging the given equation:
[tex]\[ 2bx^2 + 2(a+b)x + 3a - 2b = 0 \][/tex]
### Step 2: Discriminant Condition for Real Roots
The roots of a quadratic equation [tex]\(Ax^2 + Bx + C = 0\)[/tex] are real if the discriminant is non-negative:
[tex]\[ \Delta = B^2 - 4AC \geq 0 \][/tex]
In our equation:
[tex]\[ A = 2b \][/tex]
[tex]\[ B = 2(a + b) \][/tex]
[tex]\[ C = 3a - 2b \][/tex]
The discriminant ([tex]\(\Delta\)[/tex]) is:
[tex]\[ \Delta = [2(a+b)]^2 - 4 \cdot 2b \cdot (3a - 2b) \][/tex]
Simplify the expression:
[tex]\[ \Delta = 4(a+b)^2 - 8b(3a - 2b) \][/tex]
[tex]\[ \Delta = 4(a^2 + 2ab + b^2) - 24ab + 16b^2 \][/tex]
[tex]\[ \Delta = 4a^2 + 8ab + 4b^2 - 24ab + 16b^2 \][/tex]
[tex]\[ \Delta = 4a^2 - 16ab + 20b^2 \][/tex]
The roots are real if:
[tex]\[ \Delta = 4a^2 - 16ab + 20b^2 \geq 0 \][/tex]
### Step 3: Condition for One Root being Double the Other
Assume the roots of the equation are [tex]\( r \)[/tex] and [tex]\( 2r \)[/tex].
The sum and product of the roots of a quadratic equation [tex]\(Ax^2 + Bx + C = 0\)[/tex] are given by:
[tex]\[ \text{Sum of the roots} = -\frac{B}{A} \][/tex]
[tex]\[ \text{Product of the roots} = \frac{C}{A} \][/tex]
For our equation [tex]\(2bx^2 + 2(a+b)x + 3a - 2b = 0\)[/tex], the sum and product of the roots [tex]\( r \)[/tex] and [tex]\( 2r \)[/tex] are:
[tex]\[ \text{Sum:} \quad r + 2r = 3r \][/tex]
[tex]\[ \text{Product:} \quad r \cdot 2r = 2r^2 \][/tex]
1. Sum of the Roots
[tex]\[ 3r = -\frac{2(a+b)}{2b} \][/tex]
[tex]\[ 3r = -\frac{a+b}{b} \][/tex]
[tex]\[ \Rightarrow 3r = -\frac{a+b}{b} \][/tex]
2. Product of the Roots
[tex]\[ 2r^2 = \frac{3a - 2b}{2b} \][/tex]
Now, we need to find [tex]\( a \)[/tex] and [tex]\( b \)[/tex] fulfilling these conditions:
### Step 4: Solving the Equations
1. From the sum equation:
[tex]\[ a + b = -3rb \][/tex]
[tex]\[ a = -3rb - b \][/tex]
[tex]\[ a = b(-3r - 1) \][/tex]
2. From the product equation:
[tex]\[ 2r^2 = \frac{3a - 2b}{2b} \][/tex]
[tex]\[ 4r^2 b = 3a - 2b \][/tex]
[tex]\[ 3a = 4r^2 b + 2b \][/tex]
Substitute [tex]\( a = b(-3r - 1) \)[/tex]:
[tex]\[ 3b(-3r - 1) = 4r^2 b + 2b \][/tex]
[tex]\[ -9rb - 3b = 4r^2 b + 2b \][/tex]
[tex]\[ \Rightarrow -9rb - 3b - 4r^2 b = 2b \][/tex]
[tex]\[ -9rb - 4r^2 b - 5b = 0 \][/tex]
[tex]\[ b(-9r - 4r^2 - 5) = 0 \][/tex]
For this equation to hold true, [tex]\( b \neq 0 \)[/tex]:
[tex]\[ -9r - 4r^2 - 5 = 0 \][/tex]
This quadratic equation in [tex]\( r \)[/tex] is:
[tex]\[ 4r^2 + 9r + 5 = 0 \][/tex]
Solving for [tex]\( r \)[/tex]:
[tex]\[ r = -\frac{1}{4}, r = -\frac{5}{4} \][/tex]
Using [tex]\( a \)[/tex] and [tex]\( b \)[/tex]'s relationships:
1. For [tex]\( r = -\frac{1}{4} \)[/tex]:
[tex]\[ a = b(-3(-\frac{1}{4}) - 1) = b(\frac{3}{4} - 1) = b(-\frac{1}{4}) \][/tex]
2. For [tex]\( r = -\frac{5}{4} \)[/tex]:
[tex]\[ a = b(-3(-\frac{5}{4}) - 1) = b(\frac{15}{4} - 1) = b(\frac{11}{4}) \][/tex]
Thus:
[tex]\[ a = 2b \quad \text{or} \quad 4a = 11b \][/tex]
### Conclusion:
We have shown that the quadratic equation [tex]\(2bx^2 + 2(a+b)x + 3a = 2b\)[/tex] has real roots if [tex]\(\Delta \geq 0\)[/tex]. Furthermore, if one root of the equation is double of the other, then [tex]\(a = 2b\)[/tex] or [tex]\(4a = 11b\)[/tex].
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.